1995
DOI: 10.1046/j.1365-2648.1995.22010048.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the level of student reflection from reflective journals

Abstract: The concept of reflective learning has been widely adopted in many of the nursing curricula today. Reflective learning is of particular relevance to the education of professionals, as it encourages students to integrate theory with practice, appreciate the world on their own behalf, and turn every experience into a new potential learning experience. While nurse educators have widely accepted the educational benefits of reflection, research into reflective learning is hampered by the lack of reliable and widely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
310
1
8

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(345 citation statements)
references
References 12 publications
16
310
1
8
Order By: Relevance
“…Medicine, nursing, and pharmacy are among the disciplines that are adapting these types of reflective processes in curricula to aid in learning as well as improve patient care. [13][14][15][16][17][18][19][20][21] The extent of medical residents' reflection has been explored [13][14][15] and showed that physicians' decision-making skills were improved in complex clinical cases if they were able to critically reflect on those experiences. 15 An evaluation of nursing students concluded that interview sessions (individual, paired, and group) on reflective practice were viewed as beneficial for the participating students and encouraged them to practice reflective thinking on their own.…”
Section: Discussionmentioning
confidence: 99%
“…Medicine, nursing, and pharmacy are among the disciplines that are adapting these types of reflective processes in curricula to aid in learning as well as improve patient care. [13][14][15][16][17][18][19][20][21] The extent of medical residents' reflection has been explored [13][14][15] and showed that physicians' decision-making skills were improved in complex clinical cases if they were able to critically reflect on those experiences. 15 An evaluation of nursing students concluded that interview sessions (individual, paired, and group) on reflective practice were viewed as beneficial for the participating students and encouraged them to practice reflective thinking on their own.…”
Section: Discussionmentioning
confidence: 99%
“…All team members attended an orientation session on the coding system and the procedure for analyzing journal content. [21] The identification of these principles was essential to ensure structure and consistency among the team members. The coding principles (see Table 3) included the following: repeated points or arguments are coded only once; if a coder perceives that a student is between coding stages within a paragraph, the coding is based on the lower stage of the coding system; coding is only valid with evidence or substantiation; coding must be supported by textual data and quotes from the literature to illustrate or substantiate a student's own experience are amenable to coding, but quotes that merely demonstrate textbook knowledge are not coded; concepts in the student journals that pertain to personal issues are excluded from coding and finally coders must maintain a personal log to validate their decision making.…”
Section: Methodsmentioning
confidence: 99%
“…[10,17,18] Similarly, student-reaction essays were also used as a method to guide medical students in exploring and clarifying misconceptions, values, and attitudes concerning aging and palliative care. [19] These studies and others have demonstrated the utility of using Mezirow's theory of transformational learning, [20,21] and the affective domain [22,23] to guide reflective journaling. In particular, Wong and colleagues [21] acknowledged the lack of empirical evidence related to assessment of reflective learning.…”
Section: Reflection and Student Learningmentioning
confidence: 99%
“…Reflective learning is of particular significance to the education of nursing students as it inspires them to integrate theory and practice and through reflective writing, turns every experience into a new prospective learning experience [1]. The nursing literature focuses the need to promote the concept of reflective practice to assist students in reflection of their experiences [2][3][4][5][6].…”
Section: Review Of the Literaturementioning
confidence: 99%